Доказать, что (a+3) : (a+1) + (a+3) : 2 > или = 4, при а > 0

0 голосов
39 просмотров

Доказать, что (a+3) : (a+1) + (a+3) : 2 > или = 4, при а > 0


Алгебра (262 баллов) | 39 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Сначала упростим выражение (а+3)/(а+1)+(а+3)/2=(2а+6+а²+3а+а+3)/2(а+1)=(а²+6а+9)/2(а+1)=(а+3)²/2(а+1)

Оценим числитель
т.к.а>0, то а+3>3 ,(а+3)²>9
Оценим знаменитель
т.к.а>0,то а+1>1, 2(а+1)>2
Значит (а+3)²/2(а+1)>9/2
             (а+3)²/2(а+1)>4,5 а значит тем более (а+3)²/2(а+1)>4

Равно  4 неравенство при а>0 не может












(3.7k баллов)